Ergosterol Peroxide and Stigmasterol from The Stembark of Aglaia simplicifolia (Meliaceae) and Their Cytotoxic against HeLa Cervical Cancer Cell Lines - Nunung Kurniasih; Asep Supriadin; Desi Harneti; Rizky Abdulah; Mohamad Nurul Azmi bin Mohamad Taib; Unang Supratman (Jurnal Kimia Valensi, 2021)
Two steroid compounds, ergosterol peroxide (1) and stigmasterol (2) have been isolated from the stembark of Aglaia simplicifolia belong to Meliaceae family. The chemical structures of 1 and 2 were identified based on spectroscopic evidence including UV, IR, 1D NMR, 2D NMR as well as mass spectra and by comparison with those previously reported spectra data. Both compounds were evaluated for their cytotoxic effects against cervical cancer HeLa cells in vitro. Compounds 1 and 2 showed cytotoxicity activity against HeLa cervical cancer cells with IC50 values of 0.80 and 26.42 µM, respectively.